Clay–Polymer Nanocomposites: Chemically Specific Multiscale Modeling of Clay–Polymer Nanocomposites Reveals Intercalation Dynamics, Tactoid Self‐Assembly and Emergent Materials Properties (Adv. Mater. 6/2015). (February 2015) - Suter, James L.; Groen, Derek; Coveney, Peter V.
<x xml:space="preserve">Abstract</x> On page 966, P. V. Coveney and co‐workers show the dynamic mechanism of the intercalation of polymer molecules into the galleries of a layered clay material, simulated through a chemically specific multiscale modelling scheme. This commences at the quantum mechanical level, shown by the electronic structure of the clay edge, and systematically transfers information through an atomistic representation to a coarse‐grained description of the polymer (orange) and clay (cyan). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>